(untitled) (Archives of Mechanics - Test, 2008)
In the design of structural elements, which are used for protection against explosions, the damage evolution until failure has to be predicted in numerical simulations. However, in the literature a wide variety of damage models is available based on different approaches, e.g. phenomenological and micromechanical theories. Furthermore, the consequences of connections between new damage models and the constitutive equations accounting for elastic-viscoplasticity are unclear. The same problem occurs if structural theories, involving hypotheses, are combined with damage laws. In order to verify the calculated results, experiments with structures subjected to pressure waves are necessary. For this reason, an experimental validation method by means of shock tubes is used in the present study to verify the isotropic and anisotropic damage models. The measured deformations and experimentally observed failure modes can then be compared to the simulated results.